2013
DOI: 10.1016/j.nbd.2013.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Divergent α-synuclein solubility and aggregation properties in G2019S LRRK2 Parkinson's disease brains with Lewy Body pathology compared to idiopathic cases

Abstract: Mutations in LRRK2 are the most common genetic cause of Parkinson's disease (PD). The most prevalent LRRK2 mutation is the G2019S coding change, located in the kinase domain of this complex multi-domain protein. The majority of G2019S autopsy cases feature typical Lewy Body pathology with a clinical phenotype almost indistinguishable from idiopathic PD (iPD). Here we have investigated the biochemical characteristics of α-synuclein in G2019S LRRK2 PD post-mortem material, in comparison to pathology-matched iPD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 61 publications
(36 reference statements)
2
47
1
Order By: Relevance
“…Another interesting connection is between LRRK2 and the autophagy/lysosomal/Golgi network, because alteration of the proteolytic balance within the cell may be the reason for the build‐up of toxic aggregates of amyloidogenic α‐synuclein, as implicated in PD. Indeed, the majority of LRRK2 mutation cases show an abnormal accumulation of α‐synuclein‐positive Lewy bodies 182, although it is unclear which α‐synuclein species is more relevant in G2019S pathology 183. Identifying signalling molecules that regulate the normal and pathophysiological functions of LRRK2 is a critical unmet need for developing novel therapies and the choice of the most relevant disease models will be critical in this endeavour.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting connection is between LRRK2 and the autophagy/lysosomal/Golgi network, because alteration of the proteolytic balance within the cell may be the reason for the build‐up of toxic aggregates of amyloidogenic α‐synuclein, as implicated in PD. Indeed, the majority of LRRK2 mutation cases show an abnormal accumulation of α‐synuclein‐positive Lewy bodies 182, although it is unclear which α‐synuclein species is more relevant in G2019S pathology 183. Identifying signalling molecules that regulate the normal and pathophysiological functions of LRRK2 is a critical unmet need for developing novel therapies and the choice of the most relevant disease models will be critical in this endeavour.…”
Section: Discussionmentioning
confidence: 99%
“…This is a well-established technique to study aggregated α-syn 17, 18, 20, 21 a protein that is normally soluble in its native form but gain amyloidogenic or increased aggregation properties with disease progression or with genetic mutations. Nonetheless, some groups have used slight variations in SDS concentrations in their buffers (8% or 10% instead of 5%) 21,22,30 . The SDS is an anionic detergent and solubilises α-syn oligomers that can include membrane bound forms of α-syn, whereas urea, a chaotropic reagent denatures the insoluble aggregated and fibrillar or amyloidogenic forms of α-syn 20 .…”
Section: Discussionmentioning
confidence: 99%
“…This is done to ensure normalization of immunoblot data between several blots. This is the method adopted in our recent study 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…148,149 Interestingly, a recent study has suggested that difference in the biochemical properties of aggregated a-synuclein is produced in G2019S-linked Parkinson's disease patients when compared to those with idiopathic Parkinson's disease despite a similar histopathological presentation. 150 The reason for this is not known but implies that this mutation may promote phosphorylation of a unique set of sites within a-synuclein or that other proteins are capable of associating with the formed aggregates. What is most significant is the observation that Mn stimulates phosphorylation activity of the G2019S mutant protein, whereas it inhibits wild-type kinase activity normally activated by Mg. 151,152 Recent studies have confirmed that when LRRK2 is silenced with an shRNA, Mn can potentiate oxidative stress, leading to cell death as indicated by activation of both ROS and JNK.…”
Section: Lrrk2mentioning
confidence: 99%